An ultra-wide band printed small aperture tapered slot phased array antenna covering 6-18GHZ - NagaPavani, G.; Lakshmi Prasanna, Ch.; N.N. Sastry, Dr. (International Journal of Engineering and Technology, 2018)
For phased array applications covering ultra wide bandwidth, it is necessary to restrict the size of the aperture to less than Î»/2 at highest frequency of operation. For 6-18 GHz coverage, an aperture size of less than 9.76mm is required for scanning to Â±450 without appearance of grating lobes and occurrence of element pattern nulls over the band. Meeting this requirement a printed tapered slot antenna has been designed with the above aperture size. Detailed parametric studies have been carried out over 6-18 GHz and dimensions have been opti-mized for return loss. The design has been carried out with HFSS software. A return loss of less than -7.5dB across 5.6 - 20 GHz has been obtained for a single antenna. Also satisfactory radiation patterns have been obtained.Â